2013
DOI: 10.1002/app.39781
|View full text |Cite
|
Sign up to set email alerts
|

pH‐ and temperature‐responsive IPN hydrogels based on soy protein and poly(N‐isopropylacrylamide‐co‐sodium acrylate)

Abstract: pH‐ and temperature‐responsive interpenetrating polymer network (IPN) hydrogels based on soy protein and poly(N‐isopropylacrylamide‐co‐sodium acrylate) were successfully prepared. The structure and properties of the hydrogels were characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, differential scanning calorimetry, and thermogravimetric analyzer. The equilibrium and dynamic swelling/deswelling behaviors and the drug release properties of the hydrogels responding to pH and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Blends have many applications, but in particular they are being proposed for using in drug delivery based on polymers [2][3][4] ; or on composites [5] . pH-sensitive systems are a particular case and several materials were proposed for preparing them, including silica particles [6,7] , other inorganic particles [8] , polymeric blends [9][10][11][12] , copolymers [13][14][15] and hybrid materials [16,17] .…”
Section: Introductionmentioning
confidence: 99%
“…Blends have many applications, but in particular they are being proposed for using in drug delivery based on polymers [2][3][4] ; or on composites [5] . pH-sensitive systems are a particular case and several materials were proposed for preparing them, including silica particles [6,7] , other inorganic particles [8] , polymeric blends [9][10][11][12] , copolymers [13][14][15] and hybrid materials [16,17] .…”
Section: Introductionmentioning
confidence: 99%
“…These changes indicated the presence of the electrostatic interaction between the amine groups of CS (NH 3 + ) and the carboxyl groups of 7S (COO − ) . Additionally, compared with 7S (band at 3413 cm −1 ) and CS (band at 3425 cm −1 ), the OH stretching vibration band of 7S–CS shifted to a low wave number (band at 3374 cm −1 ); this indicated that intermolecular hydrogen bonds were also involved in the nanoparticles …”
Section: Resultsmentioning
confidence: 98%
“…An overview has been reported on developed cold‐set soy protein hydrogels for pH‐dependent controlled release of riboflavin . Similarly, pH‐responsive soy protein and poly[( N ‐isopropylacrylamide)‐ co ‐(sodium acrylate)]‐based interpenetrating polymer network hydrogels crosslinked with glutaraldehyde have been fabricated for potential applications in drug delivery . Swelling studies of the hydrogels were also conducted under different pH conditions.…”
Section: Introductionmentioning
confidence: 99%